Establishing the Chinese archaeological school : Su Bingqi and contemporary Chinese archaeology - Wang Tao
Most of what is heard in the West of Chinese archaeology is about the physical stuff Ñ the astonishing string of major finds; some, like soldiers from the Terracotta Army of the First Emperor's tumulus, have been exhibited outside China. All archaoological material is excavated, described and explained by reference to some frame of ideas. This essay on the thinking of a leading Chinese archaeologist of our day, Su Bingqi, is accompanied by an article of his in translation.